1991
DOI: 10.1038/sc.1991.36
|View full text |Cite
|
Sign up to set email alerts
|

Systematic lower limb phlebography in acute spinal cord injury in 147 patients

Abstract: SummaryThis study was concluded on paraplegic and tetraplegic patients of all aetiologies except neoplasic, where paralysis developed within 48 hours. All patients were admitted to the rehabilitation department within 90 days after the onset of paralysis. In a preliminary review of 328 files, there were 27 cases of clinical deep vein thrombosis (DVT) and 10 with pulmonary embolism (PE), 6 of which were fatal. A prospective study was conducted, based on systematic detection of asymptomatic DVT with phlebography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 12 publications
0
31
0
1
Order By: Relevance
“…Venous stasis due to forced bedrest and absence of muscle contractions, in¯ammation, frequently present in spinal cord injury patients, are known to promote venous thrombosis. 21,22 The absence of recovery of ®brinolytic potential results in loss of protection against thrombosis. This combination of risk factors explains why prophylactic anticoagulant therapy fails to provide complete protection from DVT in patients with spinal cord injury.…”
Section: Discussionmentioning
confidence: 99%
“…Venous stasis due to forced bedrest and absence of muscle contractions, in¯ammation, frequently present in spinal cord injury patients, are known to promote venous thrombosis. 21,22 The absence of recovery of ®brinolytic potential results in loss of protection against thrombosis. This combination of risk factors explains why prophylactic anticoagulant therapy fails to provide complete protection from DVT in patients with spinal cord injury.…”
Section: Discussionmentioning
confidence: 99%
“…Yelnik et al 17 reported no difference between patients with paraplegia and tetraplegia. It is interesting to note that all of our patients with paraplegia with DVT had spastic paralysis.…”
Section: 3710mentioning
confidence: 99%
“…Deep vein thrombosis (DVT) and pulmonary embolism (PE) remain common complications of spinal cord injury 1 despite widespread use of prophylactic anticoagulant therapy. 2,3 The clinical diagnosis of venous thrombosis is extremely dicult in such patients and the prevalence of thromboembolic complications has varied across studies, 4,5 in particular as a result of dierences in diagnostic methods; in the great majority of the cases, radiologic explorations are necessary particularly ultrasonography and/or phlebography.…”
Section: Introductionmentioning
confidence: 99%